Respon pertumbuhan dan hasil tanaman jagung manis (Zea mays saccharata) terhadap pupuk oganik cair orrin - Mulyati, Mulyati; Nur’aini, Nur’aini; Kusmarwiya, Rukmini (Universitas Muhammadiyah Mataram, 2022)
Orrin liquid organic fertilizer (POC) is one of the organic fertilizers that contain essential nutrients, both macro and micro, and Si elements which are readily available for plants. This study aims to determine the effect of concentration and frequency of Orrin liquid organic fertilizer on the growth and yield of sweet corn plants. The experiment was conducted on the land of a farmer in Tembeng Putik Village, Wanasaba District, East Lombok Regency. The method used is a Randomized Block Design (RBD) with a factorial pattern consisting of 2 factors: the first factor was concentration (k) Orrin Liquid Organic Fertilizer consisting of 4 levels, namely (0, 5,10, and 15) ml L-1, and the second factor was frequency (f) consisting of 2 levels, namely f1 = age of 2 and 4 weeks after planting (WAP), f2 = age of 2, 4 and 6(WAP). combinations were from these two factors were obtained 8 treatment combinations and each treatment was repeated 3 times. Data obtained were analyzed using analysis of variance at a 5% significance level, and for significantly different treatments tested further with the Honestly Significant Difference test at the same level. The results showed that there was no interaction difference between the concentration and frequency of Orrin liquid organic fertilizer on all variables tested. Orrin liquid organic fertilizer concentration did not affect all the variables tested except for the shoot fresh weight. While the frequency of Orrin liquid organic fertilizer does not affect all the variables tested. Further research is needed on the effectiveness and efficiency of using POC Orrin for the corn which can be used as an alternative to environmentally friendly fertilizers